2007
DOI: 10.1002/cbdv.200790182
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methyl Red by Water‐Hyacinth (Eichornia crassipes) Biomass

Abstract: The surface characteristics and adsorbent properties of biomass, obtained from low-cost and environmentally problematic water hyacinth, were determined. Optimum conditions for the elimination of the industrial dye Methyl Red (1) from aqueous solution were established by means of a batch adsorption technique. The ultimate adsorption capacity of water-hyacinth biomass in terms of the elimination of 1 was calculated from a Langmuir-type isotherm as 8.85x10(-2) mol g(-1) at 30 degrees and at an optimum solution pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…The linear form of the Dubinin-Radushkevich is represented by equation (5) as given below; (5) where, is related to the free energy of sorption and q m is the Dubinin-Radushkevich isotherm constants related to the degree of sorbate sorption by the activated carbon surface.  is known as Polanyi potential and it is expressed by equation (6) as follows;  = R T ln (1+ (6) where, C e is equilibrium concentration of solute and R the gas constant (Jmol -1 K -1 ) and T is the absolute temperature.A plot of against  yielding a straight line was made to confirm the model. The mean free energy of adsorption (E a ) from the Dubinin-Radushkevich equation was computed using equation (7) The sorption affinity of the activated carbon for chlorophenol FAC and CAC are 9.180 mg.g -1 and 1.968 mg.g -1 respectively indicating that the fluted activated carbon had a greater affinity for chlorophenol.The values of maximum adsorption capacity determined using the linear transformation of the Elovich equation (Table 3) is much higher than the DubininRadushkevich (Table 4).…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…The linear form of the Dubinin-Radushkevich is represented by equation (5) as given below; (5) where, is related to the free energy of sorption and q m is the Dubinin-Radushkevich isotherm constants related to the degree of sorbate sorption by the activated carbon surface.  is known as Polanyi potential and it is expressed by equation (6) as follows;  = R T ln (1+ (6) where, C e is equilibrium concentration of solute and R the gas constant (Jmol -1 K -1 ) and T is the absolute temperature.A plot of against  yielding a straight line was made to confirm the model. The mean free energy of adsorption (E a ) from the Dubinin-Radushkevich equation was computed using equation (7) The sorption affinity of the activated carbon for chlorophenol FAC and CAC are 9.180 mg.g -1 and 1.968 mg.g -1 respectively indicating that the fluted activated carbon had a greater affinity for chlorophenol.The values of maximum adsorption capacity determined using the linear transformation of the Elovich equation (Table 3) is much higher than the DubininRadushkevich (Table 4).…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…The adsorbent properties of water hyacinth biomass towards organic dyes and phenols have also been studied. Thus, Tarawou et al (2007) and Rajamohan (2009) studied the adsorption of methyl red and Congo red dyes by water hyacinth, while Khan et al (2012) and ElKhalary (2007) studied the adsorption of methylene blue onto water hyacinth biomaterial, and Woverton and McKown (1976) studied the removal of phenols from polluted water using water hyacinth biomaterial as adsorbent. In a recent paper, Mukaratirwa-Muchanyereyi et al (2015) reported on the effect of organic solvent and mineral acid treatment on the thermodynamic parameters for the adsorption of volatile n-alkane hydrocarbons n-hexane to n-decane, by water hyacinth root biomass, as typical examples of volatile non-polar organic air and water pollutants.…”
Section: Introductionmentioning
confidence: 97%
“…Generally Activated carbons are generated using materials such as; coal, wood, coconut shell, after some form of activation process (Lartey and Acqual, 1999). Recent, agricultural waste material has been adopted for production of activated carbons at temperature range of 450-700 o C (Okieimen and Wuana, 2007;Tarawou and Horsfall, 2007). The common process involved during the production of activated carbon is based on carbonizing and activating the carbonaceous at certain furnace temperature.…”
Section: Introductionmentioning
confidence: 99%